Molecular Engineering of Fluorene‐Based Hole‐Transporting Materials for Efficient Perovskite Solar Cells. Issue 6 (24th February 2022) - Jegorovė, Aistė; Momblona, Cristina; Daškevičienė, Marytė; Magomedov, Artiom; Degutyte, Rimgaile; Asiri, Abdullah M.; Jankauskas, Vygintas; Sutanto, Albertus Adrian; Kanda, Hiroyuki; Brooks, Keith; Klipfel, Nadja; Nazeeruddin, Mohammad Khaja; et al.
Abstract : New Spiro‐OMeTAD analogues and the simpler "half" structures with the terminated methoxyphenyl and/or carbazolyl chromophores are successfully synthesized under Hartwig–Buchwald amination conditions using commercially available starting materials. New fluorene‐based hole‐transporting materials combined with suitable ionization energies properly align with the valence band of the perovskite absorber. Additionally, these compounds are amorphous, which is an advantage for the formation of homogenous films, as well as eliminate the possibility for films to crystallize during operation of the devices. The most efficient perovskite solar cells devices contain carbazolyl‐terminated Spiro‐OMeTAD analogue V1267 and reach a power conversion efficiency of 18.3%, along with a short‐circuit current density, open‐circuit voltage, and fill factor of 23.41 mA cm −2, 1.06 V, and 74.0%, respectively. Moreover, "half" structures with methoxyphenyl/carbazolyl fragments show excellent long‐term stability and outperform Spiro‐OMeTAD and, therefore, hold a great prospect for practical wide‐scale applications in optoelectronic devices. Abstract : New Spiro‐OMeTAD analogues and simpler "half" compounds, bearing methoxyphenyl and/or carbazolyl chromophores, are synthesized and evaluated as hole‐transporting materials for perovskite solar cells. Their power conversion efficiencies range from 16.1% to 18.3%. Devices containing "half" compounds, bearing methoxyphenyl and carbazolyl chromophores (V1222, V1226, V1238 ), present with almost no degradation after 450 h under continuous illumination and outperform Spiro‐OMeTAD.